2010
DOI: 10.1158/1535-7163.mct-09-1077
|View full text |Cite
|
Sign up to set email alerts
|

Artemin-Stimulated Progression of Human Non–Small Cell Lung Carcinoma Is Mediated by BCL2

Abstract: We herein show that Artemin (ARTN), one of the glial cell line-derived neurotrophic factor family of ligands, promotes progression of human non-small cell lung carcinoma (NSCLC). Oncomine data indicate that expression of components of the ARTN signaling pathway (ARTN, GFRA3, and RET) is increased in neoplastic compared with normal lung tissues; increased expression of ARTN in NSCLC also predicted metastasis to lymph nodes and a higher grade in certain NSCLC subtypes. Forced expression of ARTN stimulated surviv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Luciferase Reporter Assay-Luciferase reporter assay was performed as described previously (19) using TWIST1 (20) and BCL-2 (19) promoter constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase Reporter Assay-Luciferase reporter assay was performed as described previously (19) using TWIST1 (20) and BCL-2 (19) promoter constructs.…”
Section: Methodsmentioning
confidence: 99%
“…ARTN has been reported to promote mammary [7,8], endometrial [9], lung [10] and pancreatic [11] carcinoma progression. ARTN is an estrogen-regulated gene and it has been demonstrated that ARTN reduces the efficacy of anti-estrogens in ER+MC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the expression of ARTN was demonstrated to be significantly associated with high tumor stage and poor survival. In addition, previous studies have suggested that ARTN has a role in the development and progression of diverse human carcinoma (9,10,12,2022). In pancreatic ductal adenocarcinoma, ARTN has been reported to be highly expressed compared with normal pancreases, and stimulates the invasiveness of pancreatic cancer cells (13).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the depletion of ARTN expression inhibits survival, invasion and anchorage-independent growth of both breast and endometrial cancer cells, while the forced expression of ARTN promotes these cellular behaviors (9,11). Molecularly, ARTN stimulates survival and anchorage-independent growth of human non-small cell lung cancer cells by upregulating BCL-2 expression (12). In addition, ARTN stimulates estrogen receptor-negative breast cancer cell growth, migration and metastasis by upregulating TWIST1 expression and activating the AKT pathway (21).…”
Section: Discussionmentioning
confidence: 99%